The Development of an Amorphous Approach to Ambient Cured Blended Geopolymer Mortar Mixture Design - Spano, Julian (Curtin University, 2021)
Current geopolymer formulation prescribes mixture proportions through bulk methods, considering both the inert and reactive composition of the mixture constituents. This is believe to be attributed to inconstancies in strength outcomes and production processes. This research aimed to further develop the amorphous approach to geopolymer formulation, where by geopolymer mixture proportions are prescribed with reference to the reactive composition of the feeder stocks. This research focused on binary, ternary and blended geopolymer binders within mortars.